Village Application at Pematang Serai Village Office Tanjung Pura District Langkat Regency - Kurniawan, Fahmi; Sitorus, Zulham; Arnita, Vina; Ramadhan, Aditya; Risky, Raihan (Bahasa Indonesia, 2024)
In this modern era, technology has become part of human needs, even in everyday life many people cannot be separated from technology. With technology, information is very easy to access and obtain. Various kinds of systems are made to make it easier to get and operate, one of which is by using the web. The village application system is a village administration service system that is converted from a conventional / computerized system to an information technology system in the form of a website. In this research, the village system is intended to improve the performance of village officials within the Pematang Serai Village government. The system is implemented using the MVC method which uses a native php programming model, with a combination of CSS and bosttrap. The website that was built was implemented at the Pematang Serai Village Office and was evaluated directly by the village staff to find out the shortcomings of the system to be used. With this village system, it is hoped that it can help village officials, especially the Pematang Serai Village office, in serving the administration of requests for cover letters submitted by the Pematang Serai Village community